GAGASAN EGALITARIANISME DALAM PERMAINAN TRADISIONAL BALI (DOLANAN) SEBAGAI MEDIA PENDIDIKAN KARAKTER ANAK SEKOLAH DASAR - Made Adi Nugraha Tristaningrat (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
This study aims: 1) to Integrating Dolanan in the local content of Egalitarinism is theinternalization of the value of character education into learning so that the result is an awarenessof the importance of values, and 2) to forming a positive character for children and habituationof personality values into the behavior of everyday learners through learning process both inand out of the classroom. Egalitarianism the view that man is destined to the same degree.Culture can not be separated from society. Culture has become a major feature of a group ofpeople and has been ingrained. Culture includes ideas in the human mind that are ethical andaesthetic. So in reality the culture is abstract. But its application can be observed from thebehavior, language and art owned by a community. The culture will remain as long as the membersof the community live and continue their noble culture. Along with the development of the times,technological progress also influence the cultural pattern of a society. Instead of bringing apositive impact to the culture, it is more affect the community to other cultures that in factcontradict the original culture of Indonesia. Take a look at the current trends, the minimal shirtsthat women wear, the lads who speak loudly to their parents, the cigarette smoking boy, and the